2018
DOI: 10.3389/fmed.2018.00031
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ex Vivo MRI Changes due to Progressive Formalin Fixation in Whole Human Brain Specimens: Longitudinal Characterization of Diffusion, Relaxometry, and Myelin Water Fraction Measurements at 3T

Abstract: PurposePostmortem MRI can be used to reveal important pathologies and establish radiology–pathology correlations. However, quantitative MRI values are altered by tissue fixation. Therefore, the purpose of this study was to investigate time-dependent effects of formalin fixation on MRI relaxometry (T1 and T2), diffusion tensor imaging (fractional anisotropy, FA; and mean diffusivity, MD), and myelin water fraction (MWF) measurements throughout intact human brain specimens.MethodsTwo whole, neurologically-health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 60 publications
4
70
2
Order By: Relevance
“…9 also exhibited a large spread in the same benign nodes; however, no significant correlations have been found between ADC and T2 values, as illustrated in Supporting Information Figure . Regarding the effect of fixation duration, previous studies have shown variable results depending on the tissue type . In our study, the fixation interval ranged from 2 weeks to 35 weeks (median 15 weeks); however, the correlation between MD values (or other metrics) and fixation period (r = 0.33, P = .09) was not significant.…”
Section: Discussioncontrasting
confidence: 65%
“…9 also exhibited a large spread in the same benign nodes; however, no significant correlations have been found between ADC and T2 values, as illustrated in Supporting Information Figure . Regarding the effect of fixation duration, previous studies have shown variable results depending on the tissue type . In our study, the fixation interval ranged from 2 weeks to 35 weeks (median 15 weeks); however, the correlation between MD values (or other metrics) and fixation period (r = 0.33, P = .09) was not significant.…”
Section: Discussioncontrasting
confidence: 65%
“…However, many factors including natural tissue decomposition and chemical fixation may alter the MRI properties of post‐mortem tissue causing undesirable biases in the measurement. It is known that aldehyde fixation leads to gradual shortening of T 1 /T 2 /T 2 * relaxation times, increased myelin water fraction, and apparent diffusivity reductions . The most rapid change in proton MR signal relaxation occurs during the first 3 weeks after fixation, which gradually plateaus before complete tissue penetration by the fixative agent, ~3 months after fixation .…”
Section: Introductionmentioning
confidence: 99%
“…Cohen-Adad et al observed this same delamination in electron microscopic images. 49 Shatil et al observed a nearly 150% increase in MWF in whole human brains fixed by immersion in formalin for approximately 40 days, 25 but MWI was performed without first rinsing the fixative solution out of the tissue. The presence of formaldehyde decreases the T 1 and T 2 of tissue independently of its fixative effects, which may explain the much greater increase in MWF observed by Shatil et al Formaldehyde also diffuses slowly, requiring approximately 3 to 5 weeks to penetrate and fix a whole brain specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical fixatives such as formalin form cross‐links between proteins, which decrease the T 1 and T 2 of tissue water and enhance the magnetization transfer effect . These fixation‐induced changes likely bias the myelin density measurements produced by qMT and MWI …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation